HUERISTIC RULES BASED ON A PROBABILISTIC MODEL AND A GENETIC ALGORITHM FOR RELOCATING INBOUND CONTAINERS WITH UNCERTAIN PICKUP TIMES - Tong, Xun; Woo, Youn Ju; Jang, Dong Won; Kim, Kap Hwan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Because the dwell times of inbound containers are uncertain and trucks request containers in a random order, there are many rehandling operations for containers on the top of the pickup containers. By analyzing dwell time data of various groups of inbound containers, it is possible to derive a probability distribution of each group of containers. Under the assumption that dwell times of each group of inbound containers follow a specific probability distribution, this paper discusses how to determine the locations for rehandled inbound containers during the pickup process. The overall aim of this study was to minimize the total expected number of re-handling steps for retrieving all the inbound containers from a bay. Two heuristic rules were suggested: a heuristic rule obtained from a genetic algorithm, and a heuristic rule considering the confirmed and potential re-handlings based on statistical models. A simulation study was performed to compare the performance of the two heuristic rules.